Ethnobotanical And Bioeconomy Study Of Kedung Pedut Vegetation By Javanese Community In Kulon Progo Yogyakarta - Rudin, Nur Ahmad; Rahmawati, Rini; Hidayat, Mohammad Bayu; Sawajir, Muhamad Ujang; Pramono, Bondan Agung (El-Hayah : Jurnal Biologi, 2021)
Kedung Pedut is a natural waterfall located in Menoreh Highland, Kulon Progo, Special Region of Yogyakarta, Indonesia at altitude of 529 masl. Kedung Pedut has special natural vegetation characteristics, but since 2015 tourism developments was changing the composition of vegetation in this area. This makes the ethnobotany and biobased economy study are important. Therefore, this study aims to determine the abundance and utilization of vegetation in Kedung Pedut area by Javanese community in Kulon Progo and potential utilization of various vegetation in the future. The study was carried out by grid lines method and interview. Location of vegetation sampling was along the banks of river. Identification of vegetation was carried out on tree growthform. Data analysis was done by literature studies. The results of study identified 25 species of standing vegetation in Kedung Pedut. Tree vegetation with the greatest abundance are Swietenia mahagoni (4048.05 ind/ha), Paraserianthes falcataria (1700.18 ind/ha), Cocos nucifera (1484.29 ind/ha), Bambusa blumeana (782.62 ind/ha), and Tectona grandis (701.66 ind/ha). Potential utilization of vegetation in Kedung Pedut area by Javanese community in Kulon Progo based on the development of technology and science are for medicines, agroforestry, food and beverage industry, natural dyes, furniture industry, germplasm conservation, and conservation of environment